Microbiome response to cadmium and copper ingestion in the spider Steatoda grossa (Theridiidae): short-term and long-term effects of metal intoxication - G. Wilczek; M. Malicka; K. Kasperkiewicz; J. Łukasiak; C. A. Panek; J. Strzelczyk (The European Zoological Journal)
The purpose of our study was to quantitatively and qualitatively evaluate changes in the microbiome of the opisthosoma of the spider Steatoda grossa (Theridiidae) in response to short-term (4 weeks) and long-term (12 months) exposure to copper, as a biogenic element, and cadmium, as a xenobiotic, administered under controlled laboratory conditions using Drosophila hydei flies as prey. Regardless of the duration of exposure to metals-contaminated food, their concentrations in the bodies of the tested individuals significantly exceeded control values. The highest concentration of the metals was recorded in individuals after long-term exposure (with levels exceeding those of the control by 30 times for Cd and 5 times for Cu). The presence of metals in the food had a significant effect on the qualitative and quantitative structure of the microbiome, particularly in individuals exposed to contaminated food for the short term. Spiders fed cadmium-supplemented prey exhibited a microbiome dominated by Bacillales, Enterobacteriales, Entomoplasmatales, and Burkholderiales. In contrast, Bacillales, Mycobacteriales, Bacteroidales, and Micrococcales were dominant in individuals fed copper-supplemented food for 1 month. Differences in microbiome structure between metal-treated and control individuals disappeared after 1 year of culture. Spiders cultured for 1 year, whether fed with or without metal-treated food, exhibited a microbiome rich in species diversity, with an equal distribution of individual bacterial taxa. It is possible that the microbiome itself actively participated in alleviating problems associated with food metal contamination.